Silence et langage : Genèse de la phénoménologie de Merleau-Ponty au seuil de l'ontologie - Noble, Stephen A. (Studies in contemporary phenomenology ;, 2014)
In Silence et langage Stephen A. Noble offers a new interpretation of the development of Merleau-Ponty's phenomenology which analyses the central position of language within a philosophy of perception predicated upon the interdependence of seeing and speaking.